E-Learning Adoption in Afghanistan Universities (2019-2024): A Systematic Review of Implementation, Challenges, and Future Direction - Musawi, Sayed Zabihullah; Hakimi, Musawer; Nasrat, Abdulfatah; Rahmani, Khoshal Rahman; Khaliqyar, Khudai Qul; Fazil, Abdul Wajid (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
E-learning is an approach that delivers education using digital means, wherein students access classes and resources over web-enabled devices. The study examines the integration of e-learning within Afghanistan's higher education system through a subjective research study by reviewing available literature published between 2019 and 2024 and extracted from databases such as IEEE, Springer, Science Direct, Research Gate, and Scopus. The results highlight several infrastructure barriers considered critical, which include a lack of ICT skills among both teachers and students, unstable internet access, unstable power supply situations, and a dependence on the traditional model of teaching. In addition, socio-political instability and inconsistent policies have further acted as impediments to the mass-level acceptance of e-learning.  Despite these challenges, e-learning offers opportunities for flexibility, access to different resources, and the integration of innovative teaching techniques. Cloud-based tools have proven beneficial during interruptions such as the COVID-19 pandemic, which helped in continuing education with minor interruptions. E-learning encourages independent learning and improves digital literacy, but at the same time, teachers face challenges in engaging students and supporting skill development. The disparity in internet access between the urban and rural areas aggravates the problem even further, whereby cities have more access as compared to the countryside. The study further notes that the present-day government strategies are limited in addressing e-learning, as they do not have a coherent policy framework and suffer from lack of infrastructural support. Investments in technology and teacher training are an urgent need to improve e-learning in Afghanistan.